Albright and the Gods of Mesopotamia - Hallo, William W. (The Biblical archaeologist, 1993)
How do Albright's conclusions in Yahweh and the Gods of Canaan stand up today? Many of Albright's specific results have been challenged, yet the comparative methodology that he championed remains indispensable.